Determinants and effects of microvascular obstruction on serial change in left ventricular diastolic function after reperfused acute myocardial infarction - Chung, Hyemoon; Seo, Jiwon; Kim, In-Soo; Park, Chul Hwan; Kim, Jong-Youn; Min, Pil-Ki; Yoon, Young Won; Lee, Byoung Kwon; Kim, Tae-Hoon; Hong, Bum-Kee; Rim, Se-Joong; Kwon, Hyuck Moon; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Although left ventricular (LV) diastolic dysfunction is more related to functional capacity after acute myocardial infarction (AMI), the determinants of LV diastolic functional change after reperfused AMI have not been clearly known. This study aimed to investigate the effects of microvascular obstruction (MVO) on mid-term changes in LV diastolic functional changes after reperfused AMI. Methods: In 72 AMI patients who underwent successful revascularization, echocardiography and cardiovascular magnetic resonance imaging were repeated at 9-month intervals. The late gadolinium enhancement (LGE) amount, segmental extracellular volume fraction, global LV, and left atrial (LA) phasic functions, along with mitral inflow and tissue Doppler measurements, were repeated. Results: Among the included patients, 31 (43%) patients had MVO. During the 9-month interval, LV ejection fraction and LV global longitudinal strain (GLS) were significantly improved in accordance with decrease in LGE amount (18.2 g to 10.3 g, p <0.001) and LV mass. The deceleration time (DT) of early mitral inflow (188.6 ms to 226.3 ms, p <0.001) and LV elastance index (Ed; 0.133 1/mL to 0.127 1/mL, p=0.049) were significantly improved, but not in conventional diastolic functional indexes. Their improvements occurred in both groups; however, the degree was less prominent in patients with MVO. The degree of decrease in LGE amount and increase in LV ejection fraction were significantly correlated with improvement in LV-Ed or LA phasic function, but not with conventional diastolic functional indexes. Conclusions: In patients with reperfused AMI, DT of early mitral inflow, phasic LA function, and LV-Ed were more sensitive diastolic functional indexes. The degree of their improvement was less prominent in patients with MVO.